NEW RECORD FOR IRAQI FLORA OF THE GENUS AND SPECIES MORETTIA PHILAEANA (CRUCIFERAE) IN IRAQ - O. M. Othman; R. M. Hamad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to record new genus and species (Morettia philaeana). Through field survey trips to collect the wild plants from specific places at Western Desert District of Iraq, during the year 2022 and near the Rutba Dam on Wadi Houran at Jaffalah region (28km. south west of Rutba), the species Morettia philaeana (Delile) DC. was collected as a plants of the Cruciferae family, after confirming the identification as a new species in the country depending on the Flora of the neighboring countries of Iraq, the study included the morphological description of all floral and vegetative organs, as well as the anatomy of stem and the study of some characteristics of the stomatal complex in cauline leaves . These results were confirmed by microscopic and image with a map of distribution of species individuals. In order to document the genera and species recorded process for the first time in Iraq, some of the plant samples were deposited in the Iraqi National Herbarium with numbers 60411, 60412, 60413‏, and Anbar University Herbarium with numbers 5791, 5792 and 5793. A general review of Iraqi Universities Herbaria was previously conducted, as confirmed to us new species in Iraq.